2006
DOI: 10.1007/s10681-006-9317-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of 2n pollen of Asiatic hybrid lilies by nitrous oxide treatment

Abstract: Tetraploid varieties of lilies have superior agronomic traits such as large flowers and resistance to physiological disorders. In the present study, we attempted to induce 2n pollen of Asiatic hybrid lilies by arresting the meiotic process with nitrous oxide (N 2 O) gas. To determine which meiotic stage is optimal for induction of 2n pollen, plants with attached buds at different meiotic stages were treated with N 2 O for 24 h in a pressure-tolerant cylinder. A few 2n pollen grains were induced using plants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…When most of the sampled pollen mother cells were undergoing meiotic metaphase I, buds that were of the same size as the sampled bud were treated with N 2 O for 24 h (Okazaki et al 2005;Akutsu et al 2007). …”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…When most of the sampled pollen mother cells were undergoing meiotic metaphase I, buds that were of the same size as the sampled bud were treated with N 2 O for 24 h (Okazaki et al 2005;Akutsu et al 2007). …”
Section: Plant Materialsmentioning
confidence: 99%
“…1). Previous experiments using flow cytometric analysis and crossing demonstrated that these pollen grains are diploid and can fertilize eggs (Akutsu et al 2007).…”
Section: Mode Of N 2 O Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of 2n pollen was approximately 30% larger than that of n pollen; this has been reported in Ipomoea batatas, Tulipa, Lilium, and Achillea borealis [31][32][33][34][35]. In some species, unreduced pollen is larger than n pollen by much more than 30%, such as the giant pollen grains (n = 8x) of A. borealis [35].…”
Section: Discussionmentioning
confidence: 62%
“…Numerically unreduced (2n) gametes occur occasionally in stead of the expected haploid (n) gametes and likely played a key role in formation of polyploid series (HARLAN and DE WET, 1975;DEN NIJS and PELOQUIN, 1977;VEILLEUX, 1985;RAMSEY and SCHEMSKE, 1998;RAMSEY, 2007;RIESEBERG and WILLIS, 2007). The induction of sexual polyploidization via controlled crosses between naturally occurring and aritificially induced-2n gametes have also been widely used in the breeding of forest trees (SEITZ, 1954;ZHANG et al, 2004;ZHU, 2006), potato (MENDIBURU et al, 1974;RAMANNA, 1979;CARPUTO and BARONE, 2005), grain crops (VEILLEUX, 1985;JAUHAR, 2003), fruit-bearing trees (SUGIURA et al, 2000), and ornamental plants ( VAN TUYL and LIM, 2003;AKUTSU et al, 2007).…”
Section: Introductionmentioning
confidence: 99%